Pengaruh Pelatihan Perspective Taking terhadap Perilaku Prososial Remaja Generasi Berencana (GenRe) Kota Padang - Afnan, Salsa Fadhilah; Kurniawan, Rizal (Al-DYAS, 2024)
Being able to empathize, put yourself in the position of others, and have social concern is a duty that should be held by Duta Generasi Berencana (GenRe). This study aims to test the impact of perspective taking training on improved prosocial behavior in GenRe Teens. The research uses experimental design with a pretest-posttest control group design technique. The subjects of the study were 30 youths of GenRe Kota Padang who were divided into experimental and control groups. The instruments used were prosocial behavior scales. The experimental groups were treated as perspective taking training with role play methods, while the control groups were not treated. The results of the study showed significant differences in prosocial behavior scores between the experimental group and the control group at posttest, where the prosotional scores of experimental groups were higher. It indicates that the training perspective taking effectively improves the prosocial behavior of teenagers GenRe City Padang. Thus, this training can be recommended to develop social care and behavioral aid in adolescents.